2013
DOI: 10.1111/jerd.12031
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcomes of Implant Abutments in the Anterior Region: A Systematic Review

Abstract: For the anterior region, selection of an implant with internal connection and a customized metal abutment (titanium or cast metal) can have the least mechanical complications. Limited existing clinical data indicate reduced peri-implant mucosal discoloration from zirconia abutments, which may be preferable over metal abutments, in patients with thinner mucosal tissues or patients with high or gummy smiles.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
0
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 98 publications
(96 citation statements)
references
References 48 publications
4
82
0
10
Order By: Relevance
“…36,37 Materyalin özelliğine bağlı olarak oluşan plak akümü-lasyonu ve bakteri adezyonu soncunda görülebilen periodontal dokulardaki enflamasyon ve sonrasında gelişebilen kemik kaybı, implant çevresindeki dokuların sağlığını tehdit eden faktörlerdir. 4,35 Anterior bölgedeki abutmentlerin biyolojik sonuçlarının değerlendirildiği sistematik bir derlemede, 19 27 çalışmanın 6'sında bukkal fistül rapor edilmiştir. Vida tutuculu restorasyonlarda, sadece external hex implantlarda görülmesinin olası nedeni, abutment-implant arasındaki aralığa yumuşak dokunun yürümesi olarak belirtilmiştir.…”
Section: Serami̇k Abutmentleri̇n Bi̇yoloji̇k Yönden Değerlendi̇ri̇lmesi̇unclassified
“…36,37 Materyalin özelliğine bağlı olarak oluşan plak akümü-lasyonu ve bakteri adezyonu soncunda görülebilen periodontal dokulardaki enflamasyon ve sonrasında gelişebilen kemik kaybı, implant çevresindeki dokuların sağlığını tehdit eden faktörlerdir. 4,35 Anterior bölgedeki abutmentlerin biyolojik sonuçlarının değerlendirildiği sistematik bir derlemede, 19 27 çalışmanın 6'sında bukkal fistül rapor edilmiştir. Vida tutuculu restorasyonlarda, sadece external hex implantlarda görülmesinin olası nedeni, abutment-implant arasındaki aralığa yumuşak dokunun yürümesi olarak belirtilmiştir.…”
Section: Serami̇k Abutmentleri̇n Bi̇yoloji̇k Yönden Değerlendi̇ri̇lmesi̇unclassified
“…Other factors that are of influence of a systems’ resistance to screw loosening include lubrication, screw design, screw material, and surface characteristics [16-20]. Especially implant designs with an external hex configuration are prone to abutment screw loosening [21]. …”
Section: Introductionmentioning
confidence: 99%
“…Clinical follow-ups of 1121 patients also indicated that zirconia abutments had similar biological outcomes compared with titanium abutments, namely, the plaque index, probing bleeding index, and tissue health were the same. Furthermore, the zirconia abutment showed less soft tissue recession compared with the titanium abutment [31,32].…”
Section: Zirconia As Dental Implantsmentioning
confidence: 99%